Implementasi Kampung Vertikal pada Perancangan Kawasan Kumuh Kampung Aur Kota Medan - Wildan, Ahmad; Fitri, Rahmadhani (Jurnal Teknik dan Teknologi Indonesia, 2025)
The Kampung Aur settlement is one of the slum settlements located on the banks of the Deli River in Medan City. This area frequently faces flooding and inadequate sanitation issues owing to land scarcity. Horizontal settlement upgrading is no longer feasible without eviction. This study aims to implement the vertical kampung concept as a solution to address land scarcity while preserving the local community’s socio-cultural aspects. The research method used is a qualitative method through field observation, literature studie, interview and documentation. Data collection techniques were carried out by compiling building data, analysis and vertical village design concepts. The results show that implementing a vertical kampung in Kampung Aur requires a design approach that is adaptive to flooding, as well as the vertical integration of communal spaces to adapt kampung style socializing habits.